2013
DOI: 10.1155/2013/761987
|View full text |Cite
|
Sign up to set email alerts
|

Model Organisms and Traditional Chinese Medicine Syndrome Models

Abstract: Traditional Chinese medicine (TCM) is an ancient medical system with a unique cultural background. Nowadays, more and more Western countries due to its therapeutic efficacy are accepting it. However, safety and clear pharmacological action mechanisms of TCM are still uncertain. Due to the potential application of TCM in healthcare, it is necessary to construct a scientific evaluation system with TCM characteristics and benchmark the difference from the standard of Western medicine. Model organisms have played … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…The present study carried on establishing and comparison of three KYDS rat models and found that there were similarities and differences between them. In this study, it was agreed that the symptoms and manifestations of three methods induced rats were also well in line with the diagnosis of the syndrome of kidney-yang de ciency, that is, the weakness and cold appearance of the animals were similar to those of patients with "yang de ciency" (18). Modern research has indicated that damage to HPA function was major pathological mechanisms underlying KYDS (19).…”
Section: Discussionsupporting
confidence: 69%
“…The present study carried on establishing and comparison of three KYDS rat models and found that there were similarities and differences between them. In this study, it was agreed that the symptoms and manifestations of three methods induced rats were also well in line with the diagnosis of the syndrome of kidney-yang de ciency, that is, the weakness and cold appearance of the animals were similar to those of patients with "yang de ciency" (18). Modern research has indicated that damage to HPA function was major pathological mechanisms underlying KYDS (19).…”
Section: Discussionsupporting
confidence: 69%
“…Traditional Chinese medicine (TCM) has been practiced for thousands of years in China and is well recognized in most Asian countries (S. Ling & Xu, ). However, considering the lack of fundamental studies, the use and acceptability of TCM is still significantly limited in most Western countries.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical terms, according to the holistic perspective of TCM, SQD syndrome not only refers to local digestive diseases such as chronic gastritis and irritable bowel syndrome but also contains the whole body's dysfunctions such as chronic fatigue syndrome and hypertension [ 7 – 9 ]. In experimental terms, animal models have been constructed by reserpine injection or irregular food administration [ 10 ]. Understanding the biological basis of SQD syndrome may guide the evidence-based clinical use of herbal formulae.…”
Section: Introductionmentioning
confidence: 99%